PENGEMBANGAN MODUL PROYEK PENGUATAN PROFIL PELAJAR PANCASILA PADA FASE F UNTUK MENINGKATKAN PEMAHAMAN BUDAYA MEMBATIK PADA PESERTA DIDIK [DEVELOPMENT OF A MODULE FOR PHASE F OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) TO ENHANCE STUDENTS’ UNDERSTANDING OF BATIK CULTURE] - Pratomo, Laurensia Claudia; Isnawati, Dian; Purtri Komalasari, Febyana (Polyglot, 2025)
This study aims to develop and evaluate the Project to Strengthen Pancasila Student Profile (P5) module with a local wisdom theme. The P5 activities in this module are designed to enhance students' understanding of batik culture. The Research and Development (R&D) approach using the ADDIE development model was applied in this study. However, the research was limited to the third phase of ADDIE, which is the development phase. Therefore, the ADDIE model in this research consists of the analysis phase, the design phase, and the development phase. The P5 module utilizes the dimensions of collaboration, creativity, and global diversity as indicators of the achievement of the Pancasila Student Profile. The developed module underwent validity testing by expert media validators and expert material validators. The assessment results indicate that the P5 module with the local wisdom theme is highly suitable for use in P5 activities.  Abstrak bahasa Indonesia Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi modul Proyek Penguatan Profil Pelajar Pancasila (P5) dengan tema kearifan lokal. Kegiatan P5 pada modul ini bertujuan meningkatkan pemahaman peserta didik tentang budaya batik. Research and Development (R&D) dengan model pengembangan ADDIE digunakan dalam penelitian ini. Penelitian ini dibatasi pada tahap ketiga ADDIE yaitu pengembangan, sehingga model pengembangan ADDIE dalam penelitian terdiri atas tahap analisis, tahap perancangan, dan tahap pengembangan. Modul P5 ini menggunakan dimensi gotong royong, kreatif, dan berkebhinekaan global sebagai indikator pencapaian Profil Pelajar Pancasila. Modul yang dikembangkan telah melalui uji validitas oleh validator ahli media dan validator ahli materi. Hasil penilaian yang dilakukan menunjukkan bahwa modul P5 dengan tema kearifan lokal sangat layak untuk digunakan dalam kegiatan P5.